2010
DOI: 10.1016/j.jtcvs.2009.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic ventral cardiac denervation: Does it reduce incidence of atrial fibrillation after coronary artery bypass grafting?

Abstract: Objective: This study assessed the prophylactic effect of ventral cardiac denervation on reducing atrial fibrillation after coronary artery bypass grafting. Methods: This randomized prospective study recruited 220 adult patients (aged 42-79 years) who were scheduled to undergo coronary artery bypass grafting. Of these patients, 110 underwent ventral cardiac denervation in addition to coronary artery bypass grafting and 110 underwent only coronary artery bypass grafting. The demographic, intraoperative, and pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…The estimated odds ratios, which show that patients with raised platelet counts, CRP levels, neutrophil scores, or SII had a considerably higher chance of having AF after surgery, further support the association. These results are consistent with earlier studies that link inflammation to the development and maintenance of AF [5][6][7][8][9][10][11][12][13].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The estimated odds ratios, which show that patients with raised platelet counts, CRP levels, neutrophil scores, or SII had a considerably higher chance of having AF after surgery, further support the association. These results are consistent with earlier studies that link inflammation to the development and maintenance of AF [5][6][7][8][9][10][11][12][13].…”
Section: Discussionsupporting
confidence: 93%
“…Heart surgery-induced inflammation is caused by a series of inflammatory mediators, including leukocytes and cytokines, which can cause both localized and systemic inflammation [7]. C-reactive protein (CRP) is a nonspecific acute-phase reactant that has attracted a lot of interest as one of the major markers linked to this reaction [8]. In a number of clinical contexts, elevated CRP levels, a sign of greater systemic inflammation, have been linked to a higher risk of AF [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies failed to show the benefit of cardiac denervation or found even an increase in POAF. 107109 These findings, however, do not exclude a role for sympathetic activation in the arrhythmia substrate, as both sympathetic and parasympathetic activation alter atrial refractoriness. 109,110 Hogue et al .…”
Section: Mechanisms Based On Acute Factorsmentioning
confidence: 96%
“…107109 These findings, however, do not exclude a role for sympathetic activation in the arrhythmia substrate, as both sympathetic and parasympathetic activation alter atrial refractoriness. 109,110 Hogue et al . 103 detected a higher HRV in some patients, but a lower HRV in others in the hour before onset of POAF, suggesting the possibility of divergent autonomic conditions shortly before onset of the arrhythmia.…”
Section: Mechanisms Based On Acute Factorsmentioning
confidence: 96%